2019
DOI: 10.1101/747170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimization of AsCas12a for combinatorial genetic screens in human cells

Abstract: Cas12a enzymes have attractive properties for scalable delivery of multiplexed perturbations, yet widespread usage has lagged behind Cas9-based strategies. Here we describe the optimization of Cas12a from Acidaminococcus (AsCas12a) for use in pooled genetic screens in human cells. By assaying the activity of thousands of guides, we confirm on-target design rules and extend them to an enhanced activity variant, enAsCas12a. We also develop the first comprehensive set of off-target rules for Cas12a, and demonstra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…7c). Considering these and additional enCas12a variants (Gao et al, 2017;Kim et al, 2016;Tóth et al, 2018;Kleinstiver et al, 2019;Sanson et al, 2019) renders approx. 97% of all human genes accessible for C-terminal PCR tagging (Fig.…”
Section: Crrna Design Pam Site Selection and Genomic Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…7c). Considering these and additional enCas12a variants (Gao et al, 2017;Kim et al, 2016;Tóth et al, 2018;Kleinstiver et al, 2019;Sanson et al, 2019) renders approx. 97% of all human genes accessible for C-terminal PCR tagging (Fig.…”
Section: Crrna Design Pam Site Selection and Genomic Coveragementioning
confidence: 99%
“…The protospacer sequence should preferably not contain four or more 'T'-s in a row, since this might lead to premature termination of the Pol III transcription of the crRNA (Arimbasseri et al, 2013) In practice, we observed that crRNAs with 'TTTT' are frequently functional. PAM sites are ranked according to literature (Gao et al, 2017;Kim et al, 2016;Tóth et al, 2018;Kleinstiver et al, 2019;Sanson et al, 2019). In addition, unconventional PAM sites were considered (MCCC for the AsCas12a RR variant and RATR for LbCas12a RVR variant), based on depositor comments on the Addgene webpage.…”
Section: Sequencementioning
confidence: 99%
“…Given the limitations of this computational approach, we sought to expand our knowledge of paralog buffering through systematic dual-gene CRISPR knockout screening. Cas12a, formerly Cpf1, offers an endogenous RNA endonuclease function that enables processing and utilization of multiple gRNA from a single polycistronic transcript (Zetsche et al, 2015) and the modified enCas12a enzyme offers superior performance in genetic screens in mammalian cells (Kleinstiver 140 et al, 2019;Sanson et al, 2019). A key advantage of this system is that specific guide pairs can be synthesized in a single oligo, allowing one-step library design, a major advantage over multiplex Cas9 systems (Cong et al, 2013;Kabadi et al, 2014;Chen et al, 2015;Shen et al, 2017).…”
mentioning
confidence: 99%
“…Illumina-compatible guide array amplicons were amplified from gDNA in one step, as described in Sanson et al, 2019). Indexed PCR primers were synthesized by Integrated DNA Technologies 80 μg represents at least 500 cells per guide array for these hypotriploid cell lines (www.ATCC.org).…”
mentioning
confidence: 99%
“…MARC dramatically simplifies in vivo screening, thus promising to democratize it and unleash its full power: the PiggyBac constructs and transgenic mice can be made within weeks and months, respectively; the screening is done in situ, requiring no ex vivo manipulation but only routine procedures such as TAM administration and cell isolation; the key reagent (mice), once created, is self-perpetuating (via simple breeding); diverse cell types are targetable, including those inaccessible to viral libraries; the targeting can be global or spatiotemporal-specific depending on Cas9 expression patterns, offering flexibility in the experimental design; and finally, several distinct transgenes can be bred together and consolidated into a single mouse line, to reduce the screen scale (Peets et al, 2019) and more importantly, to enable combinatorial screens and hence the uncovering of genetic interactions (Sanson et al, 2019;Shen et al, 2017).…”
Section: Marc For In Vivo Genetic Screensmentioning
confidence: 99%